PENGARUH KEPEMIMPINAN, MOTIVASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA YANG BERDAMPAK PADA PRESTASI KERJA - Rizki Kurniawan; Ahmad Yani Hazir (LPPM STIE PERTIBA Pangkalpinang, 2019)
This study aims to analyze the influence of leadership, motivation, work environment, organizational culture on performance both simultaneously and partially. Furthermore, to analyze the effect of performance on the performance of employees of the Land Office of Central Bangka Regency. The amount of sample determined is 30 employees of the Land Office of Central Bangka Regency. The research instrument used questionnaires, arranged on a scale of 1-5, score 1 for very poor responses and a score of 5 for excellent responses. The method of analysis using path analysis (Path analysis) trimming model. Hypothesis testing using F test (simultaneous) and t-test (partial). The result of this research concludes that there is significant influence from the variable of leadership, motivation, work environment, organizational culture to motivation 97,3%. Furthermore, for performance variables, there is a positive and significant impact on employee performance which is seen from the coefficient of determination by 75 percent. Furthermore, to the Land Office of Central Bangka Regency to improve the variables of leadership, motivation, work environment, organizational culture in order to increase the motivation that can give a positive influence on employee performance